ПОЛОНІЙ-210 – ПЕРСПЕКТИВНИЙ ПРИРОДНИЙ РАДІОТРАССЕР ТРОФІЧНИХ ТА ПАРАЗИТОЛОГІЧНИХ ЗВ’ЯЗКІВ ЧОРНОМОРСЬКОГО ШПРОТА - Лазоренко, Г. Є.; Полікарпов, Г. Г.; Гаєвська, А. В.; Корнійчук, Ю. М. (Marine Ecological Journal, 2023)
210Ро concentrations in the Black Sea sprat, its organs and larvae of nematode Hysterothylacium aduncum were determined. It was shown that this radionuclide can be used as a natural indicator of trophic and parasitological connections of the sprat.